Outcomes valued by people living with dementia and their carers: A qualitative systematic review with a qualitative synthesis. (December 2021) - Booi, Laura; Wheatley, Alison; Brunskill, Greta; Banerjee, Sube; Manthorpe, Jill; Robinson, Louise; Bamford, Claire
Abstract: Background: Growing numbers of interventions are being developed to support families living with dementia, but the extent to which they address the issues of most importance to people living with dementia and their carers is unclear. The aim of this review is to synthesise the best available qualitative evidence on the outcomes valued by (a) people living with dementia and (b) their carers, both for themselves and each other. This review is a part of a wider project aiming to improve post diagnostic support for people living with dementia and their carers. Method: We will use thematic synthesis methodology. Studies from 1990 onwards will be eligible if they include qualitative data on the views of people living with dementia or their carers on valued outcomes or the lived experience of dementia. Databases to be searched include MEDLINE, CINAHL, PsycInfo and Social Sciences Premium Collection, in addition to systematically gathered grey literature. Rayyan QCRI software will be used to manage the screening processes and NVivo software will be used to manage data extraction and analysis. The review will also critically evaluate the extent to which international recommendations address the areas of importance to people living with dementia and their families. Results: The results of this review will be presented at the conference. Conclusion: The findings will be of relevance to researchers, policy makers, and providers and commissioners of dementia services.